Correlation between interlamellar amorphous structure and gas permeability in poly(lactic acid) films. Issue 16 (11th March 2014) - Sato, Shuichi; Nyuui, Tatsuki; Matsuba, Go; Nagai, Kazukiyo
ABSTRACT We have investigated the relationship between amorphous structure and its gas permeability of poly(lactic acid) (PLA) using differential scanning calorimetry, wide‐angle X‐ray scattering, and small‐angle X‐ray scattering measurements. We focused on the hierarchical interlamellar amorphous structure of various gas‐permeable PLA films. The films crystallized just above Tg did not have any long‐spacing period peaks at the room temperature even with the existence of crystals; conversely, peaks could be observed from long spacing periods with heating. Therefore, the interlamellar amorphous density became as high as crystalline region one at the room temperature. These high‐density amorphous regions, the so‐called rigid‐amorphous phase, reduced the gas diffusion and permeation. In the case of samples crystallized above 90°C, the long spacing period peaks could be observed even at the room temperature. The amorphous region did not develop the rigid‐amorphous phase, and the gas permeability depended only on crystallinity. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40626.